Increased risk of temporomandibular joint disorders and craniofacial deformities in patients with juvenile idiopathic arthritis: a population-based cohort study. Issue 11 (November 2022) - Ma, K.S.-K.; Thota, E.; Huang, J.-Y.; Wei, J.C.-C.; Resnick, C.M.
Abstract: Juvenile idiopathic arthritis (JIA) is an autoimmune disease that has been proposed to involve the temporomandibular joint (TMJ). The aim of this study was to identify the relationships between JIA, TMJ disorders, and craniofacial deformities. This cohort study included patients diagnosed with clinically active JIA between 1999 and 2013 through a nationwide longitudinal health registry. The primary outcome was the presence of a TMJ disorder. The secondary outcome was the presence of a JIA-associated craniofacial deformity. A total of 2791 patients with JIA were included in the case group; 11, 164 propensity score-matched individuals without JIA were selected from the same database as controls. TMJ disorders were present in 142 individuals: 48 (1.72%) in the case group and 94 (0.84%) in the control group (relative risk 2.047, 95% confidence interval 1.446–2.898). Craniofacial deformities were present in 374 individuals: 112 (4.01%) in the case group and 262 (2.35%) in the control group (relative risk 1.722, 95% confidence interval 1.380–2.148). Patients with JIA showed a significantly greater likelihood of developing TMJ disorders and craniofacial deformities compared to matched controls.